The value of literary work in full formation: the inssue of (in)discipline (Olhar de Professor, 2023)
This article reflects on the importance of literature as an instrument in the integral formation of subjects, in addition to favoring the acquisition of diverse contents, with emphasis on the issue of (in)discipline, starting from the teachers' and students' enchantment with reading. The research is qualitative, of a bibliographic nature. The work O Ateneu (Crônica de saudades) by Raul Pompéia (1863–1895) has been used, published in 1888, it is considered one of the most renowned novels in Brazilian literature, which brings us elements that demonstrate the educational system of the time. The challenges experienced throughout the history of education are analyzed through the contribution of ideas from authors such as Freinet, Durkheim, Hunt and Werneck that corroborate to achieve the objective of the article. Our conclusion is that the school needs to be studied from the perspective of its time and that the challenge of making education a value for the subject can be the result of integral education.
Keywords: Education. Literature. Integral formation. (In)discipline.